2012
DOI: 10.1227/neu.0b013e31822dda12
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Results With a New Telemetric Intracranial Pressure-Monitoring System

Abstract: This new telemetric system was safe and effective for ICP measurement over a long period, including home monitoring. For the patients, it was easy to handle, and reliable data could be recorded over many weeks. Based on this preliminary experience, the authors consider the new system extremely advantageous in surgical decision making in particularly difficult cases of suspected abnormalities of ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
0
29
0
3
Order By: Relevance
“…Published initial clinical experiences with the device, as well as results on zero drift, have been favorable. 13 In that study, 4 probes explanted after 14, 15, 16, and 28 days all showed a zero drift of 0 mm Hg. Measurements were obtained for as long as 180 days after implantation, without incident.…”
Section: Surgery and The Telemetric Devicementioning
confidence: 82%
“…Published initial clinical experiences with the device, as well as results on zero drift, have been favorable. 13 In that study, 4 probes explanted after 14, 15, 16, and 28 days all showed a zero drift of 0 mm Hg. Measurements were obtained for as long as 180 days after implantation, without incident.…”
Section: Surgery and The Telemetric Devicementioning
confidence: 82%
“…"smart" valves with telemetry and pressure sensors that do not drift, 33,34,88,92,111,131 reinforced kink-resistant catheters, and suture-less connectors.…”
mentioning
confidence: 99%
“…In contrast, several publications reported for the recently introduced Neurovent-P-tel ICP measurement system (Raumedic, Helmbrechts, Germany) more promising results. Welschehold et al [15] presented their first clinical experiences after implanting the Neurovent-P-tel in 10 patients. They described a comfortable handling, no severe complications associated with the implantation and no significant zero-point drift detectable in the atmospheric pressure environment after explantation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Welschehold et al [15] presented their first clinical experiences after implanting the Neurovent-P-tel in 10 patients. They described a comfortable handling, no severe complications associated with the implantation and no significant zero-point drift detectable in the atmospheric pressure environment after explantation [15]. In an experimental study, Orakcioglu et al [10] referenced the telemetric Neurovent-P-tel against the conventional externalized Neurovent-P pressure sensor in a porcine model.…”
Section: Discussionmentioning
confidence: 99%